Emotional Intelligence, Work Fatigue, and Work Life Balance as Drivers of Employee Performance: An Islamic Human Resource Management Perspective : (Evidence from the Community Empowerment Agency of Bandar Lampung City) - Tegar Semidang Jaya; Ahmad Habibi; Yeni Susanti (Mabsya: Jurnal Manajemen Bisnis Syariah, 2026)
This study examines the influence of emotional intelligence, job fatigue, and work-life balance on employee performance from the perspective of Human Resource Management (MSDI). The research was conducted on employees of the Community Empowerment Office in Bandar Lampung using a quantitative approach with questionnaires as the primary data collection tool. Data were analyzed using multiple regression to determine the partial and simultaneous effects of the independent variables. The results show that emotional intelligence has a positive and significant effect on performance, as employees with strong emotional regulation and interpersonal skills tend to be more effective in their tasks. Job fatigue negatively affects performance by reducing motivation and work quality, while work-life balance has a positive contribution by helping employees maintain harmony between professional and personal life. From the MSDI perspective, these findings emphasize that employee performance improvement requires not only technical competence but also emotional stability, workload management, and balance in life aspects. Organizations need to pay attention to these factors to enhance effectiveness and the quality of public services.